Evaluation of minimally invasive sampling methods for detecting Avipoxvirus: Hummingbirds as a case example - Galvin, Aoife N.; Pandit, Pranav S.; English, Simon G.; Quock, Rachel C.; Bandivadekar, Ruta R.; Colwell, Rita R.; Robinson, Barbara W.; Ernest, Holly B.; Brown, Mollie H.; Sehgal, Ravinder N. M.; Tell, Lisa A. (Frontiers in Veterinary Science, 2022)
Avian pox is a common avian virus that in its cutaneous form can cause characteristic lesions on a bird’s dermal surfaces. Detection of avian pox in free-ranging birds historically relies on observations of visual lesions or histopathology, which can underestimate avian pox prevalence. We compared traditional visual observation methods for avian pox with these molecular methods that utilize minimally invasive samples in an ecologically important group of birds, hummingbirds. Specifically, avian pox prevalence in several species of hummingbirds were examined across multiple locations using three different methods: 1) visual inspection of hummingbirds for pox-like lesions from a long-term banding data set, 2) qPCR assay of samples from hummingbird carcasses from wildlife rehabilitation centers, and 3) qPCR assay of samples from live-caught hummingbirds. A stark difference in prevalences among these three methods was identified, with an avian pox prevalence of 1.5% from banding data, 20.4% from hummingbird carcasses, and 32.5% from live-caught hummingbirds in California. This difference in detection rates underlines the necessity of a molecular method to survey for avian pox, and this study establishes one such method that could be applied to other wild bird species. Across all three methods, Anna’s Hummingbirds harbored a significantly higher avian pox prevalence than other species examined, as did males compared with females and birds caught in Southern California compared with Northern California. After hatch-year hummingbirds also harbored higher avian pox prevalences than hatch-year hummingbirds in the California banding data set and the carcass data set. This is the first study to estimate the prevalence of avian pox in hummingbirds and address the ecology of this hummingbird-specific strain of avian pox virus, providing vital information to inform future studies on this charismatic and ecologically important group of birds.